Canonical Correlation Analysis and Its Extension for SSVEP-based BCI Detection: A Systematic Review - Muhamad Agung Suhendra; Iqbal Robiyana; Tedi Sumardi; Ahmad Sofyan Sulaeman; Permono Adi Putro; Nurizati Nurizati; Usep Tatang Suryadi; Anderias Eko Wijaya; Sunanto Ajidarmo; Arief Budiman; M. Faizal Amri (Postgraduate, University of Mataram, 2024)
SSVEP-based Brain-Computer Interfaces (BCIs) utilize steady-state visual evoked potentials, which are brain responses triggered by visual stimuli flickering at specific frequencies. Users can focus on these stimuli, allowing the system to interpret their intent based on the brain's electrical activity. This technology has applications in communication for individuals with disabilities, gaming, and neuro-feedback, offering an ultimate means of interaction through thought alone. In this study, systematic literature review was conducted to identify analytical methods for SSVEP spellers with PRISMA method from the eligibility criteria. CCA and its extension become gold-standar method that give excellent performances for SSVEP recognition and signal classification. Some uniques features also found such as MsetCCA, FB-CCA, MF-CCA, TW-CCA, CP-CCA, IIS-CCA, TT-CCA and RLS-CCA. Therefore, we have various options for choosing the best method for recognizing SSVEP from EEG signals based BCI.